Exploring the Interfaces between Ethnobiology and Ecotoxicology: A Novel Approach - Graziela Dias Blanco; Natalia Hanazaki; Suelen Beeck Cunha; Marta Jussara Cremer; Mari Lucia Campos (Ethnobiology Letters, 2020)
In recent years, increases in urbanization and industrialization have led to an increase in contaminated areas, which directly affect traditional, indigenous, and local communities who use natural resources for food and medicine. We present a discussion about the use of food resources from areas contaminated with heavy metals and focus on two case studies in southern Brazil.  In the first case study, we interviewed 194 residents about the use of plants as food resources or medicine in areas adjacent to abandoned mines, and thus potentially contaminated with heavy metals. In the second case study, we interviewed 39 fishers about the consumption of fish resources from areas potentially contaminated by industrial activities. We also asked about their perceptions regarding contamination, changes in the landscape, and health problems that could be related to contamination. Although people are aware of contamination, consuming local plants and sea food has not stopped because some of these practices are directly linked to their cultural identity; additionally, there might be a lack of public recognition toward contamination. The combination of ethnoecological and ecotoxicological studies is necessary to assess environmental problems caused by heavy metals, as well as concerns about food security and the health of local communities.